Comparison of Ultrasound-Guided Core Needle Biopsy Under the Assistance of Hydrodissection With Fine Needle Aspiration in the Diagnosis of High-Risk Cervical Lymph Nodes: A Randomized Controlled Trial - Teng, Dengke; Dong, Chunhui; Sun, Daju; Liu, Zhuo; Wang, Hui (Frontiers in Oncology, 2022)
A randomized comparison of ultrasound (US)-guided core needle biopsy (CNB) under the assistance of hydrodissection with fine needle aspiration (FNA) was performed to evaluate the feasibility, safety and effectiveness for the diagnosis of high-risk cervical lymph nodes. Patients from December 2018 to May 2020 were randomly assigned to the CNB group and the FNA group at a ratio of 1:1. This study protocol was approved by the Ethics Committee of our hospital and registered in the Chinese Clinical Trial Registry (ChiCTR1800019370). The feasibility of CNB for high-risk cervical lymph nodes was evaluated by observing and recording the separation success rate (SSR) and technical success rate (TSR) of the CNB group. Safety was evaluated by comparing the incidence of major complications in the two groups. The diagnostic efficacy was evaluated by comparing the diagnostic accuracy, sensitivity, and specificity of the two groups. A total of 84 patients (84 lymph nodes) were randomized into the CNB (n = 42) and FNA (n = 42) groups. All patients in the CNB group achieved successful hydrodissection and biopsy. The SSR and TSR were both 100% in the CNB group. There were no major complications during or after the process in the two groups. Compared with the FNA group, the CNB group was significantly superior in terms of diagnostic accuracy and sensitivity (100% vs. 81.0%, P = 0.009; 100% vs. 79.2%, P = 0.035, respectively). The specificity of the two groups was 100%, and there was no significant difference. Compared with FNA, CNB under the assistance of hydrodissection is a feasible and safe method but is more effective for the diagnosis of high-risk cervical lymph nodes.